Ireland : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2017)
This Selected Issues paper provides an overview of income distribution and the welfare system in Ireland, with a focus on the crisis and postcrisis periods. Ireland's flexible economy and strong social safety net helped mitigate the adverse effects of the property-driven crisis. Although economic conditions are improving rapidly, lifting employment, ongoing efforts are needed to address the lingering impact on those hardest hit, including the long-term unemployed and unemployed youth. Consistent efforts are needed to support sustainable and inclusive growth and meet ambitious social targets, including the reduction of consistent poverty to 2 percent by 2020.